Beach Mice - Brittany L. Bird; Lyn C. Branch; Mark E. Hostetler (EDIS)
This document is WEC 165, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2002.